Nivel de información y depresión en mujeres histerectomizadas por cáncer de cervix en el Hospital Virgen de la Puerta, Trujillo - Torres Torres, Irina Rocío (2019)
The present investigation is of a descriptive, correlational, cross-sectional type, whose objective was to establish the relationship between the level of information and depression in hysterectomized women due to cervical cancer at the Virgen de la Puerta Hospital. The sample consisted of 30 women, the instruments were used: Evaluation of the level of information of the hysterectomized woman, prepared by the author and the Beck Depression Inventory. The results showed that 60% of hysterectomized women have regular information level, 23.33% good level and 16.67% low level; as for the level of depression, 40% are slightly depressed, 26.67% moderately depressed, 16.66% severely depressed and 16.67% without depression. When the variables were correlated using the chi-squared test, it was found that the level of information and depression had a highly significant statistical relationship (p <0.001).